Incidence and clinical features of extramedullary multiple myeloma in patients who underwent stem cell transplantation. (1st April 2015) - Weinstock, Mathew; Aljawai, Yosra; Morgan, Elizabeth A.; Laubach, Jacob; Gannon, Muriel; Roccaro, Aldo M.; Varga, Cindy; Mitsiades, Constantine S.; Paba‐Prada, Claudia; Schlossman, Robert; Munshi, Nikhil; Anderson, Kenneth C.; et al.
Summary Extramedullary disease (EMD), defined as an infiltrate of clonal plasma cells at an anatomic site distant from the bone marrow, is an uncommon manifestation of multiple myeloma. Six hundred and sixty‐three consecutive patients with multiple myeloma who underwent stem cell transplantation between January 2005 and December 2011 were assessed for the presence of EMD. A cohort of 55 patients with biopsy‐proven EMD was identified, comprising 8·3% of the total study population. EMD was present at the time of diagnosis in 14·5% of cases and at the time of relapse in 76% of patients. The most common EMD presentations at relapse were liver involvement and pleural effusions. EMD specimens had high expression of CD44 (92%) and moderate expression of CXCR4. The median overall survival from time of myeloma diagnosis was 4·1 years (95% CI: 3·1, 5·1) and the median overall survival from time of EMD diagnosis was 1·3 years (95% CI: 0·8, 2·3). This report demonstrates that the incidence of EMD has not increased with the introduction of novel agents and stem cell transplantation. The most common EMD presentations in the relapsed setting were liver and pleural fluid. The presence of CD44 and CXCR4 expression may represent new markers of EMD that warrant further investigation.